FIRM SIZE AS A MODERATING VARIABLE ON AUDIT DELAY FACTORS ANALYSIS - I Made Ryan Ananta Putra; Made Gede Wirakusuma (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
The variety of audit of completion time from the closing date of the financial 12 months to the date of issuance of the audit file is referred to as audit postpone. The rate in finishing the audit gives a fine signal to investors. The cause of this examine turned into to determine the effect of profitability and leverage on audit put off with firm length as moderation. The have a look at become conducted on meals and beverage organizations listed at the inventory trade as many as 7 groups with non-chance sampling, method purposive sampling technique. Records collection by way of non-participant observation, thru www.idx.co.identity. The records analysis method used is MRA. The consequences show that firm size isn't a moderator of the effect of profitability on audit delay and firm length is capable of moderate the effect of leverage on audit postpone. The studies implication is that businesses with strong internals supply a tremendous signal and replicate that the employer complies with policies.